PENERAPAN STRATEGI PERMAINAN SEBAGAI UPAYA PEMBELAJARAN SECARA INOVATIF DALAM BAHASA JERMAN - Lia Malia (Jurnal Cakrawala Pendidikan, 2001)
Learning of foreign language means trying to understand the structure and the use oflanguage. The teaching of foreign languages, German in particular, would help the learners toachieve the aim.The games are meant to activate the, learner's structure and vocabulary. The effectiveinvolvement of learners in game increases the result of the learning as well as retention.Through games, anxiety to be involved in speaking commonly experienced by learners willcertainly disappear. Learners can be involved in spontaneous speaking activities. Games inforeign language learning not only games but a form of practices.